Sustainable competitive advantage in Construction: Study of Central Region of Parana - Brunetti, Mário Luis; Teixeira, Gylmar; de Castro, Marcos; Lara, Luiz Fernando (REBRAE, 2015)
In the fierce market competition, the companies need different strategies that give them a competitive advantage that may result from resources controlled by organization. In this way, search linked to the resource based view (RBV), well founded by Penrose (1959), Wernerfelt (1984) and Barney (1991), allow identifying those resources able to generate competitive advantage. This article seeks to identify the sources of sustainable competitive advantage in the constructing companies in the center-western region of Parana State, through a qualitative research approach we investigated three companies in this sector which are located in the central region of Parana State. For data analysis, we used the VRIO model developed by Barney (2007). In this model, some resources stand out as potential generators of competitive advantages when they are valuable, rare, inimitable and organizational within the context in which they are introduced. The results have shown that companies which operate in this line of business are dependent primarily of ten essential resources and two are introduced as potential sources of sustainable competitive advantage: 1) Experience and track record in the market; 2) Structure, organization and planning.